Socio-economic inequalities in utilization of dental services in households of Lorestan province and comparing it with neighboring provinces - Sajad GHorbanizadeh; Fatemeh Tajar; Zahra Asadi Piri; Satar Rezaei; Yaser Mokhayeri; Soraya Nouraei Motlagh (Tehran University of Medical Sciences, 2021)
Introduction: Socio-economic inequalities in the use of dental services are a major challenge to health policies in many countries. This cross-sectional study was conducted to investigate socio-economic inequalities in utilization of dental services in households of Lorestan province and comparing it with neighboring provinces. Methods: Data required for the study were collected from the household expenditure and income survey (HIES). The study population included 5547 households in the western provinces of the country. Logistic regression method was used to determine the most important factors affecting the use of dental services, and the focus index was used to measure inequality between income groups. Data analysis was performed using Stata software version 14. Results: The highest and lowest percentages of dental services among households were related to Hamedan (7.02%) and Lorestan (3.19%) provinces, respectively. The results of the focus index showed that the benefits and costs of dental services were concentrated among households with higher socio-economic status. In other words, inequality benefits the rich. Being a female head of household and increased size of the household leads to a decrease in the use of these services. The higher education level of the head of the household and the increase in the number of employed and literate household members showed a positive relationship with the utilization of dental services. Conclusion: Benefiting from dental services was significantly higher among higher socio-economic groups. These inequalities can be avoided by introducing and implementing targeted policies. Low-income households, lower education levels, and the unemployed should be the focus of health policies to address unmet dental care needs.